YES AND: A Generative AI Multi-Agent Framework for Enhancing Diversity of Thought in Individual Ideation for Problem-Solving Through Confidence-Based Agent Turn-Taking - Ghosh, Pratik; Rintel, Sean (CHI 2025, 2025)
Diversity of thought is crucial in ideation for problem-solving, yet professionals in organisational settings often face challenges such as limited access to varied expertise and resource constraints which hinder the ideation process. To address this issue, we propose YES AND, a Generative AI based multi-agent framework that simulates diverse perspectives through AI agents for ideation with a single user. Leveraging a unique confidence-based turn-taking model, these agents organically take turns as they build on ideas, pose clarification questions to the user for improved contextual understanding, and allow the user to interject and steer the conversation. Beyond addressing the limitations of traditional ideation, this framework offers a novel approach to leveraging Generative AI for ideation, moving away from the rigidity of pre-defined interaction rules towards a more dynamic and creative process that enables serendipitous development of ideas.